Perinatal outcome in cases of isolated single umbilical artery and its effects on neonatal cord blood gas indices. (October 2014) - Doğan, S.; Özyüncü, Ö.; Atak, Z.; Turgal, M.
Abstract We aimed to evaluate perinatal outcomes and blood gas indices of isolated single umbilical artery (SUA). In this retrospective study, 134 fetuses with SUA were evaluated. A total of 77 (57.4%) fetuses with isolated SUA (iSUA) were compared with maternal age-matched 95 fetuses with double umbilical arteries (DUA), with respect to pregnancy outcome and umbilical cord blood gas indices. The incidence of SUA in our cohort was 1.04%. Patients with iSUA had lower neonatal birth weight compared with the control group (2, 635 ± 972 g vs 2, 991 ± 669 g; p = 0.009). Small for gestational age (SGA) frequency was higher in the group of iSUA when compared with fetuses with DUA (17.4% vs 5.4%; p = 0.03). Regarding the umbilical cord blood gas, the parameters were comparable between the two groups. SUA has a favourable obstetric outcome as long as the accompanying malformations are ruled out. Furthermore, neonatal cord blood gas parameters in fetuses with iSUA do not differ from fetuses with DUA.